Influence of the Safe Behavior Program on the Workers of the Callao Plant -CLSA, Lima-Peru - Rodríguez Del Carpio, César (2020)
Behavior-based safety programs are applied with the aim of reinforcing the level of safety at work, but if it is done by complying with a number of observations of safe behavior established in the goal of the month in the workplace, it generates in workers who only comply with safety while being observed or that observers report behaviors that they did not really see; consequently, accidents with workers continue and even worse with fatal cases, observers stop believing in the safety program they are using and management comes to believe that with a greater number of observations it is possible to correct unsafe behaviors; therefore, the results of the program are not achieved over time. This is a consequence of not having understood the principles of behavior-based security theory since the beginning of its implementation. In the present investigation, the behavior-based security theory was applied to define the observer card and to carry out positive reinforcement interventions efficiently. Thus, the study aimed to find out if there is a significant difference between the observations of safe behavior before the observer performs the feedback with positive reinforcement and the observations after each intervention, for this, only the number of safe observations was taken for the purpose of To know the effect of the positive reinforcement feedback that occurs in the observation of safe behaviors in the study period. It was found that there is a significant difference in safe behaviors after performing the feedback for a confidence level of 95% and a reduction of 85.7% of disabling accidents in the study period.